Maria Wnęk and all her saints - Observations about the exhibitionat Gardzienice Gallery in Lublin - Welcz, Henryk (Current Problems of Psychiatry, 2014)
Maria Wnęk has left many works, most originated from the years 1973-1991 situated in the private collections, the galleries and museums in Poland and abroad. It is interesting that there is no extensive knowledge about her, and a similar situation is with other Polish art brut artists. Present in these works inspirations with the folk culture and iconic painting are probably no longer so surprising and original like 30 years ago, when they were created. The presence of the schizophrenic features in these artistic expressions is connected with the long-lasting psychotic process. The influences of folk culture characteristic for the Wnęk’s region are not surprising. The religiousness of Maria Wnęk connected with the traditions of Kalwaria Zebrzydowskia is reflected in many of her works. The analysis of her creation, same as of the described earlier Edmund Monsiel’s works, is the perfect lesson of psychopathology for the young psychiatrists and a very interesting subject for the art historians.